2019
DOI: 10.3390/ijerph16081414
|View full text |Cite
|
Sign up to set email alerts
|

Data Collection Instruments for Obesogenic Environments in Adults: A Scoping Review

Abstract: The rise in obesity prevalence has increased research interest in the obesogenic environment and its influence on excess weight. The aim of the present study was to review and map data collection instruments for obesogenic environments in adults in order to provide an overview of the existing evidence and enable comparisons. Through the scoping review method, different databases and webpages were searched between January 1997 and May 2018. Instruments were included if they targeted adults. The documents were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 117 publications
(102 reference statements)
0
14
0
Order By: Relevance
“…The emergence and fast rise of the obesity epidemic during the last few decades is often attributed to exposure to 'obesogenic' neighbourhood environments [14,15], that is, environments with an urban design and built form that dissuade or inhibit physical activity, and/or a food environment that makes choosing healthy and nutritious food difficult or unaffordable. Studies examining associations between obesogenic environments and physical activity have reported that activity is higher in more walkable, more compact, and less sprawling neighbourhoods [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…The emergence and fast rise of the obesity epidemic during the last few decades is often attributed to exposure to 'obesogenic' neighbourhood environments [14,15], that is, environments with an urban design and built form that dissuade or inhibit physical activity, and/or a food environment that makes choosing healthy and nutritious food difficult or unaffordable. Studies examining associations between obesogenic environments and physical activity have reported that activity is higher in more walkable, more compact, and less sprawling neighbourhoods [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…The identification of the obesogenic environment has been conducted using quantitative methods such as observational questionnaires (audits, checklists, systematic social observation), surveys or government health reports, geographic information systems (GIS) and/or questionnaires capturing the perception of individuals [9]; qualitative methods were also used through focus groups or the photovoice technique [10][11][12][13]. The importance of determining which elements constitute these obesity-generating environments has led to the development of data collection instruments [9,[14][15][16][17][18]. However, data collection instruments that consider the perception people have of their food environment are scarce [9].…”
Section: Introductionmentioning
confidence: 99%
“…The importance of determining which elements constitute these obesity-generating environments has led to the development of data collection instruments [9,[14][15][16][17][18]. However, data collection instruments that consider the perception people have of their food environment are scarce [9]. Some research has shown that perception is a mediator between the exposure to the environment and the interaction of people with it [5,19].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations